Lexical and syntactic alignment during English-Spanish teletandem meetings. (December 2022) - Michel, Marije; Appel, Christine; Cipitria, Saioa
Abstract: First language (L1) interactants quickly develop a coordinated form of communication, reusing each other's linguistic choices and aligning to their partner (Pickering & Garrod, 2021). More recently, research became interested in second language (L2) alignment (cf., Kim & Michel, this issue). Earlier work has shown that both lexical and syntactic alignment can be found in L2 dialogue, with task type and context as potential mediating factors (e.g., Dao, Trofimovich, & Kennedy, 2018). This study adds to the existing work on alignment in second language production by exploring task effects in English-Spanish teletandem conversations. Twenty-nine English-Spanish tandem pairs completed video-based free conversation and Spot-the-Difference tasks, alternating the language of communication: both participants acted as L2 learner and as L1 expert in turns. The 174 task performances were scrutinized for alignment by identifying the number of overlapping lexical and syntactic n-grams (cf., Michel & Smith, 2018). We compared alignment between paired students (i.e., real pairs) to 'coincidental overlap' in created conversations of randomly combined speaker pairs. Results showed significantly more alignment by real than random pairs, and more syntactic than lexical alignment, while task effects were mixed. We discuss our findings in light of telecollaborative task-based interaction as support for L2 development. Highlights: Video-based English-Spanish teletandem interaction comparing free vs. task-based conversations. Novel methodology comparing alignment in real pair conversations with randomly paired conversations demonstrating that alignment is not coincidental. Generally, more morphosyntactic than exact lexical alignment. More alignment of tokens than types, suggesting a repetition of the same structures. Trends suggest more lexical alignment in task-based than free conversation.